2011
DOI: 10.4103/0256-4947.81538
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense and oxidative stress in children with acute hepatitis A

Abstract: BACKGROUND AND OBJECTIVES:Published data on oxidative stress in children with acute hepatitis A are still very scarce. This study aims to evaluate the oxidant/antioxidant status of these patients.DESIGN AND SETTING:Prospective, case-control study, over 2.5 years in patients under hospitalized and ambulatory care.PATIENTS AND METHODS:The levels of a whole-blood antioxidant, reduced glutathione; and plasma antioxidants, β-carotene, retinol, ascorbic acid, α-tocopherol; and the biomarker of oxidative stress, malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…It was determined that pro‐oxidant/antioxidant imbalance can cause oxidative damage on cellular molecules. Additionally, oxidative stress was related to cardiovascular, infectious diseases, cancer, diabetes mellitus, and neurodegenerative pathologies . In different childhood diseases, many biochemical tests measuring the oxidative status, TOS and TAC were shown to be practical, inexpensive, and reliable .…”
Section: Discussionmentioning
confidence: 99%
“…It was determined that pro‐oxidant/antioxidant imbalance can cause oxidative damage on cellular molecules. Additionally, oxidative stress was related to cardiovascular, infectious diseases, cancer, diabetes mellitus, and neurodegenerative pathologies . In different childhood diseases, many biochemical tests measuring the oxidative status, TOS and TAC were shown to be practical, inexpensive, and reliable .…”
Section: Discussionmentioning
confidence: 99%
“…In old patients with chronic hepatitis, at the beginning of the disease, a marked depletion of GSH is observed [117]. Additionally, Cemek et al [145] and Popovic-Dragonjic et al [146] found decreased GSH levels in children with chronic hepatitis.…”
Section: Hepatitis E Virus (Hev) and Hepatitis A Virus (Hav)mentioning
confidence: 99%
“…The main sources of ROS in hepatocytes in acute or chronic disease are mitochondria and cytochrome P450 enzymes. Oxidative stress, as the consequence of increased intracellular ROS concentrations, can be reduced by antioxidants, such as vitamin A, vitamin C, vitamin E and reduced glutathione 171,198 …”
Section: Viral Infections and Mitochondrial Involvementmentioning
confidence: 99%
“…Oxidative stress, as the consequence of increased intracellular ROS concentrations, can be reduced by antioxidants, such as vitamin A, vitamin C, vitamin E and reduced glutathione. 171 , 198 …”
Section: Viral Infections and Mitochondrial Involvementmentioning
confidence: 99%